2014
DOI: 10.1002/ana.24187
|View full text |Cite
|
Sign up to set email alerts
|

Defining a therapeutic target for pallidal deep brain stimulation for dystonia

Abstract: Our results provide a map of the region of influence of therapeutic DBS for dystonia and represent a potential target to refine current methods of surgical planning and stimulation parameters selection. Based on their role in alleviating symptoms, these regions may also provide anatomical and physiological information relevant to disease models of dystonia. Further experimental and clinical studies will be needed to validate their importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…Algorithms that allow one to identify the ideal contact and stimulation parameters based on neuroimaging, brain connectivity, and modeling of the stimulation field could represent a major advance for programming DBS in dystonia in the near future (e.g. Figure 2) 17 .…”
Section: Dbs Programmingmentioning
confidence: 99%
“…Algorithms that allow one to identify the ideal contact and stimulation parameters based on neuroimaging, brain connectivity, and modeling of the stimulation field could represent a major advance for programming DBS in dystonia in the near future (e.g. Figure 2) 17 .…”
Section: Dbs Programmingmentioning
confidence: 99%
“…In principle, the process involves exploring various montages (dose) with the goal of identifying a current flow pattern that best supports the presumed mechanism of action or experimental hypothesis (Wongsarnpigoon and Grill, 2012). However, how to select a "best" target and consider collateral brain current flow (side effects) is an open question (Cheung et al, 2014;Fytagoridis et al, 2013) because the relationship between brain current flow patterns and cognition is complex. One solution, which is implicitly adopted in many reports though not made explicit, is the quasi-uniform assumption.…”
Section: Step 1: Forward Models Of Current Flowmentioning
confidence: 99%
“…In addition to patient-specific DBS data, decision support systems for DBS tuning may also make use of historical population-specific data. Historical population-specific data has been used in a number of studies to create and visualize probabilistic stimulation maps (PSMs) related to therapeutic as well as side effects of stimulation [19-26]. It has been shown that model-based approaches, with and without PSMs, can assist selection of the clinically best electrode contacts and increase the efficiency of programming [27-29].…”
Section: Introductionmentioning
confidence: 99%